Mechanism of Resistance in Mungbean [Vigna radiata (L.) R. Wilczek var. radiata] to bruchids, Callosobruchus spp. (Coleoptera: Bruchidae) - War, Abdul R.; Murugesan, Surya; Boddepalli, Venkata N.; Srinivasan, Ramasamy; Nair, Ramakrishnan M. (Frontiers in Plant Science, 2017)
Mungbean (Vigna radiata (L.) R. Wilczek var. radiata) is an important pulse crop in Asia, and is consumed as dry seeds and as bean sprouts. It is an excellent source of digestible protein. Bruchids [Callosobruchus chinensis (L.) and Callosobruchus maculatus (F.)] are the important pests of mungbean and cause damage in the field and in storage. Bruchid infestation reduces the nutritional and market value of the grain and renders seeds unfit for human consumption, agricultural and commercial uses. These pests are controlled mainly by fumigation with highly toxic chemicals such as carbon disulphide, phosphene, and methyl bromide, or by dusting with several other insecticides, which leave residues on the grain, thus, threatening food safety. Some plant-based extracts have been found useful in controlling bruchids, but are not fully successful due to their short-term activity, rapid degradability, and potentially negative effect on seed germination. Although some wild sources of bruchid resistance in mungbean have been reported, which have been used to develop bruchid- resistant lines, undesirable genetic linkages threaten the proper exploitation of genetic diversity from wild germplasm into commercial cultivars. Further, biotype variation in bruchids has rendered some mungbean lines susceptible that otherwise would have been resistant to the pest. Host plant resistance is a cost-effective and a safe alternative to control bruchids in mungbean and is associated with morphological, biochemical and molecular traits. These traits affect insect growth and development, thereby, reduce the yield losses by the pests. Understanding the defense mechanisms against insect pests could be utilized in exploiting these traits in crop breeding. This review discusses different traits in mungbean involved in defense against bruchids and their utility in pest management. We also highlight the breeding constraints for developing bruchid-resistant mungbean and how can these constraints be minimized. We further highlight the importance of supporting conventional breeding techniques by molecular techniques such as molecular markers linked to bruchid resistance.